THE IMPORTANCE OF SPIRITUAL AND MORAL IDEAS IN MYSTICISM IN EDUCATING YOUNG PEOPLE IN ENLIGHTENMENT - Mukhsimov Davron Tulkunovich (American Journals Publishing, 2022)
The article covers the doctrine of mysticism, which has a special place in the spiritual life of the peoples of Central Asia, its moral educational ideas are reflected in its importance in the education of young people in modern society
Keywords: orif, dhikr, fana, sufsim, madhab, shafqat, generosity, religion, Quran, Sunna